Novel Oxygen Carrier Slows Infarct Growth in Large Vessel Occlusion Dog Model Based on Magnetic Resonance Imaging Analysis. Issue 4 (22nd March 2022) - Shazeeb, Mohammed Salman; King, Robert M.; Anagnostakou, Vania; Vardar, Zeynep; Kraitem, Afif; Kolstad, Josephine; Raskett, Christopher; Le Moan, Natacha; Winger, Jonathan A.; Kelly, Lauren; Krtolica, Ana; Henninger, Nils; et al.
Abstract : Background: Tissue hypoxia plays a critical role in the events leading to cell death in ischemic stroke. Despite promising results in preclinical and small clinical pilot studies, inhaled oxygen supplementation has not translated to improved outcomes in large clinical trials. Moreover, clinical observations suggest that indiscriminate oxygen supplementation can adversely affect outcome, highlighting the need to develop novel approaches to selectively deliver oxygen to affected regions. This study tested the hypothesis that intravenous delivery of a novel oxygen carrier (Omniox-Ischemic Stroke [OMX-IS]), which selectively releases oxygen into severely ischemic tissue, could delay infarct progression in an established canine thromboembolic large vessel occlusion stroke model that replicates key dynamics of human infarct evolution. Methods: After endovascular placement of an autologous clot into the middle cerebral artery, animals received OMX-IS treatment or placebo 45 to 60 minutes after stroke onset. Perfusion-weighted magnetic resonance imaging was performed to define infarct progression dynamics to stratify animals into fast versus slow stroke evolvers. Serial diffusion-weighted magnetic resonance imaging was performed for up to 5 hours to quantify infarct evolution. Histology was performed postmortem to confirm final infarct size. Results: In fast evolvers, OMX-IS therapy substantially slowed infarct progression (by ≈1 hour, P <0.0001) and reduced the final normalized infarct volume as compared to controls (0.99 versus 0.88, control versus OMX-IS drug, P <0.0001). Among slow evolvers, OMX-IS treatment delayed infarct progression by approximately 45 minutes; however, this did not reach statistical significance ( P =0.09). The final normalized infarct volume also did not show a significant difference (0.93 versus 0.95, OMX-IS drug versus control, P =0.34). Postmortem histologically determined infarct volumes showed excellent concordance with the magnetic resonance imaging defined ischemic lesion volume (bias: 1.33% [95% CI, −15% to 18%). Conclusions: Intravenous delivery of a novel oxygen carrier is a promising approach to delay infarct progression after ischemic stroke, especially in treating patients with large vessel occlusion stroke who cannot undergo definitive reperfusion therapy within a timely fashion.